Exploring the intrinsic dimensions of study abroad aspirations: The case of Vietnamese international students in Japan - Nhi, Tran Lam Thien (Journal of International Students, 2025)
This paper focuses on aspirations to study abroad, using the case of Vietnamese international students (VISs) in Japan. A qualitative research study based on 23 in-depth interviews applied the ‘aspirations-capabilities’ framework (de Haas, 2021) and revealed that while economic factors play a significant role in motivating Vietnamese students to study abroad, the ‘intrinsic’ dimension of migration aspirations, such as personal well-being and the desire to live abroad, also heavily influences their aspirations. They initially prioritize practical benefits, which can overshadow the importance of intrinsic values. However, it is crucial to consider both the instrumental and intrinsic dimensions, as they often overlap and cannot be separated. Ignoring the intrinsic dimension would overlook the complexity of the reasons behind VIS aspirations. Focusing on the case of VIS in Japan, this study contributes to a deeper and more nuanced understanding of why they study abroad.